A methodology for the assessment of the knock mitigation potential of a port water injection system. (1st January 2021) - Millo, F.; Mirzaeian, M.; Rolando, L.; Bianco, A.; Postrioti, L.
Highlights: Numerical assessment of knock mitigation potential of water injection. Innovative indexes for knock mitigation and risk of oil dilution were developed. Experimental validation of innovative indexes was performed. Optimization of water injection pressure, phasing and targeting was performed. Abstract: The introduction of innovative spark ignition engines featuring extreme downsizing, high compression ratio and Miller Cycle has led to an increasing interest in water injection as one of the most promising countermeasures to reduce the knock risk. In this paper, the potential of a Port Water Injection (PWI) system integrated in a state-of-the-art turbocharged downsized spark ignition engine was investigated through both numerical simulations and experiments. A 3D-CFD water spray model, properly calibrated against experimental data, was used to predict water spray evaporation and to evaluate the engine oil dilution risk. On the basis of the 3D CFD analysis, two new indexes were specifically defined and correlated with experimental data to evaluate the effectiveness of water injection in terms of knock mitigation and the risk of engine oil dilution. After assessing their reliability by means of a sensitivity analysis on both calibration parameters and hardware configurations, the proposed indexes were successfully exploited to perform a preliminary design and optimization of the water injection system.